Synthesis and Antimicrobial Evaluation of some Functionalized Heterocycles Derived from Novel Quinolinyl Chalcone. (13th July 2017) - Hassan, Mohamed M.; Farouk, Osama
Abstract : The reaction of 3‐acetyl‐4‐hydroxyl‐1‐methylquinolin‐2(1 H )‐one(1) with 10‐oxo‐4, 6, 7, 8, 9, 10‐hexahydropyrazolo[1, 5‐ a ][1]benzothieno[2, 3‐ d ]pyrimidine‐3‐carbaldehyde(2) afforded the novel enone system3 . The latter compound was reacted with some 1, 2‐binucleophilic reagents to give pyrazoline derivative4 and isoxazoline derivative5 . Treatment of chalcone3 with 1, 3‐binucleophilic reagents afforded pyrimidine and thiazine derivatives6 –8 . Moreover, reaction of compound3 with active methylene reagents furnished pyridine, pyran, and cyclohexanone derivatives9 –12 . Cyclization of compound12 by using hydrazine hydrate yielded indazol‐3‐one derivative13. On the other hand, the cyclocondensation of the enone3 with 1, 4‐dinucleophilic reagents yielded diazepine derivative14 and triazolothiadiazepine derivative15 .The characterization of the newly synthesized heterocyles were confirmed on the basis of their elemental analysis and spectral data (IR, NMR, and MS). These compounds were also screened for their antibacterial activities. Abstract :